20th century precipitation trends in the Yangtze river catchment - Stefan Becker; Marco Gemmer; Tong Jiang; Chanqing Ke (Justus-Liebig-Universität Gießen, Zentrum für Internationale Entwicklungs- und Umweltforschung (ZEU), 2003)
Research on climate trends in China has been carried out within a co-operation of the Justus Liebig Universities Department of Geography and Zentrum für internationale Entwicklungs- und Umweltforschung (ZEU) and Chinese colleagues of the Nanjing Institute of Geography and Limnology (CAS) and Nanjing University. Earlier Sino- German studies of this co-operation focused on historical climate variability (CHEN et al. 1997; CHEN et al. 2001). Climate trend analysis with observed data was started in 2002 during exchange programmes of the Chinese co-authors which were funded by the German Academic Exchange Service (DAAD) and the International Bureau of the Federal Ministry of Education and Research (BMBF-IB). The exchange was part of the project on “Sustainable Land Use, Flood Risks and Watershed Ecosystem Management” of the ZEU's section 1. The results of the author's precipitation and temperature trend research has been published as BECKER et al. (2003a), BECKER et al. (2003b), BECKER et al. (2003c), and GEMMER et al. (2003). Furthermore, the results were presented in poster sessions at following international conferences: International Symposium on Climate Change (ISCC), 31 March - 3 April, 2003, Beijing, China, and Chinese-German Workshop on Climate Change and Yangtze Floods. 4-8 April 2003, Nanjing, China. The paper in hand presents yet unpublished materials which came into being while working out the international publications. It is supposed to give a closer glance at actual research activities at the Department of Geography and the ZEU.
Keywords: 330